2022
DOI: 10.1111/ffe.13793
|View full text |Cite
|
Sign up to set email alerts
|

On micro‐defect induced cracking in very high cycle fatigue regime

Abstract: It is known that fine granular area morphology is often formed around interior micro-defect in the case of very high cycle fatigue failure of high strength steel.The mechanism of "fragmentation of martensitic laths and formation of dislocation cells" (Zhu's model), which revealed a microstructure-dependent crack initiation and early growth for micro-defect induced internal fatigue cracking, was discussed in several lathy martensitic or similar steels, verified under environmental fatigue, and applicable to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…A fatigue crack initiation origin with an FGA near the sample surface has been observed. Different from earlier studies, 4–8,15–21 the fatigue crack initiation origin with an FGA observed here occurred in the matrix without any defect. This means that the fatigue damage and consequently the formation of fatigue crack initiation origin can mainly be related to the material behavior.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…A fatigue crack initiation origin with an FGA near the sample surface has been observed. Different from earlier studies, 4–8,15–21 the fatigue crack initiation origin with an FGA observed here occurred in the matrix without any defect. This means that the fatigue damage and consequently the formation of fatigue crack initiation origin can mainly be related to the material behavior.…”
Section: Resultscontrasting
confidence: 99%
“…This mechanism provides a confirmation of the interesting models on the formation of FGA at a subsurface inclusion recently 7,15,19,21,45 . However, the current study provides a fundamental understanding of how material damage and crack initiation occur in a material matrix during VHCF.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Gan et al 16 applied a variant of the ANN model, called extreme learning machine, for fatigue life prediction considering the mean stress effect. Zhu et al 17 used an ML‐based method combined with a physics‐based parameter to evaluate the fatigue life of four materials in the very high‐cycle fatigue regime. Nashed et al 18 developed a probabilistic neural network (PNN) and evaluated it using case studies available in the literature.…”
Section: Introductionmentioning
confidence: 99%